Reduced Antarctic ozone depletions in a model with hydrocarbon injections - Cicerone, RJ; Elliott, S; Turco, RP (Science, 1991)
Motivated by increased losses of Antarctic stratospheric ozone and by improved understanding of the mechanism, a concept is suggested for action to arrest this ozone loss: injecting the alkanes ethane or propane (E or P) into the Antarctic stratosphere. A numerical model of chemical processes was used to explore the concept. The model results suggest that annual injections of about 50,000 tons of E or P could suppress ozone loss, but there are some scenarios where smaller E or P injections could increase ozone depletion. Further, key uncertainties must be resolved, including initial concentrations of nitrogen-oxide species in austral spring, and several poorly defined physical and chemical processes must be quantified. There would also be major difficulties in delivering and distributing the needed alkanes.